Juridical Analysis Of Restorative Justice In Peaceful Settlement Of Cases - Edi Rahmat Susanto; Cahyo, Cahyo (Sean Institute, 2024)
The handling of criminal cases using a restorative justice approach is a specific and dynamic interactive relationship between the parties involved. The restorative justice movement has great potential to reform the way society responds to crime and wrongdoing. Restorative Justice is a shift in criminalization in the criminal justice system that prioritizes justice for victims and perpetrators of criminal acts, in addition to alternative punishments such as social work and others. The formulation in this study is How is restorative justice regulated according to applicable laws and regulations? What is the ideal concept of restorative justice in case settlement in Indonesia? The research method used in this study is a normative juridical research method, the result of the discussion in this study is that restorative justice is an effort to resolve criminal cases that is oriented towards restoring relationships between victims and perpetrators and their respective families as well as the community whose processes are carried out in accordance with laws and regulations both at the investigation or investigation level, the prosecution level and at the general justice level Law enforcement institutions and officials at every level of the criminal case settlement process facilitate, process and make minutes to ensure that the settlement of criminal cases is based on restorative justice and the ideal concept of restorative justice is a concept that provides justice value for both perpetrators and victims.